Experimental feasibility study of a new attached hydronic loop design for geothermal heating of bridge decks. (5th January 2020) - Yu, Xinbao; Hurley, Mark Timothy; Li, Teng; Lei, Gang; Pedarla, Aravind; Puppala, Anand J.
Highlights: A new hydronically heated bridge deck was developed for existing bridges. Hydronic loops encapsulated in a geofoam layer were attached to a concrete slab. Surface heat flux varied from 120 to 270 W/m 2 at the test conditions. An empirical equation was developed to predict slab temperature. The heated slab design is efficient and feasible to prevent bridge icing. Abstract: Geothermally heating of bridges is a green and sustainable alternative to deicing chemicals, which are energy-intensive, corrosive to the bridges, and dangerous to the environment. Geothermal bridges harness shallow earth geothermal energy, a readily available all-year-round renewable energy source. However, the existing geothermal heated bridge technology was developed based on embedded hydronic loops, which can be only deployed during the construction of new bridges. As there are more existing bridges in the critical need of deicing, a new attached hydronic loop design was developed in this study for geothermal heating of existing bridges. The hydronic loops are attached to the bottom of a bridge deck and are encapsulated inside an insulation material geofoam. The developed hydronic loop was tested on a lab-scale concrete deck with supplied warm water to evaluate its feasibility for field application. This heated deck system was fabricated and instrumented for the heating performance tests in an environmental chamber. It was first tested under various room temperatures higher than 4.4 °C, the lowest temperature permitted by the environmental chamber. Based on the test results, an empirical prediction equation is presented to estimate deck temperature at given ambient and supplied heating fluid temperatures. The applicability of this equation to freezing temperature was validated in localized freezing tests by placing a cooling box on the test deck. All test results show that this heated bridge deck allows efficient heat transfer, approximately 60% of the supplied heat, to the bridge deck surface. The supplied heat flux to the deck surface ranges from 120 to 270 W/m 2 depending on the ambient and heating fluid temperature, which is comparable to the embedded hydronic system. The new hydronic loop design is feasible to be implemented on the existing bridges for deicing and snow removal.